Morphological and Physico-Mechanical Properties of Nano-Graphene-Oxide from Sugarcane Bagasse for Polymer Composite Reinforcement - Onovo, Harrison Okechukwu; Agbeleye, Ademola Abiona; Akano, Theddeus Tochukwu; Oyegbami, Solomon Onaolapo; Orafunam, Kenechukwu Joshua; Odediran, Olugbenga Peter (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
Graphene oxide (GO) from biomass offers a sustainable alternative to conventional graphite, yet few studies explore sugarcane bagasse (SB) as a feedstock. This research fills that gap by synthesizing GO from SB termed SBGO and reinforcing epoxy composites with it. Mature SB from Lagos, Nigeria, was processed, oxidized using KMnO₄/H₂SO₄, and purified with H₂O₂ and water washes. SBGO was characterized by BET, TEM, FTIR, UV–Vis, XRD, and Raman spectroscopy. BET analysis revealed a high Langmuir surface area of 579.3 m²/g and mesopores averaging 2.132 nm, favoring uniform dispersion. TEM showed SBGO particles ranging from 5–10 nm up to 30–40 nm agglomerates with irregular, flake-like morphologies. FTIR confirmed successful oxidation via prominent O–H (3200–3600 cm⁻¹), C=O (1700–1740 cm⁻¹), and C–O (1000–1300 cm⁻¹) peaks, while UV–Vis displayed a π–π* peak near 230 nm and an n–π* shoulder around 300 nm, evidencing successful oxidation. XRD patterns exhibited a peak at 25°–30°, indicating partial restoration of the graphitic structure. Raman spectra featured dominant D and G bands, with additional peaks at 568, 1818, 2034, 2208, 2874, and 3050 cm⁻¹ that signal defects and residual biomass features. Polymer composites (PC) with 0–2.0 g SBGO showed increased density (from 1.18 to 1.23 g/cm³) and reduced porosity (from 1.67% to 0.75%). Tensile strength and modulus peaked at 1.5 wt% SBGO, hardness rose from 20.9 to 26.1 VHN, and wear rate dropped by up to 58%. These results confirm that SB-derived GO is an effective, eco-friendly reinforcement that enhances composite strength and durability for high-performance applications.